2012
DOI: 10.3382/ps.2012-02470
|View full text |Cite
|
Sign up to set email alerts
|

Commercially available amino acid supplementation of low-protein diets for broiler chickens with different ratios of digestible glycine+serine:lysine

Abstract: This work studied the effect of supplementing commercially available amino acids in low-protein diets using different ratios of digestible (dig) glycine+serine:lysine (Gly+Ser:Lys) on performance, serum parameters, feathering, and litter characteristics of broiler chickens during the starter period. A total of one thousand fifty 1-d-old Cobb-Vantress male chicks were distributed in a completely randomized experimental design into 6 treatments with 5 replicates of 35 birds each. The treatments were as follows: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 33 publications
8
24
0
1
Order By: Relevance
“…All low-protein treatments numerically had a higher dry matter litter content than the control, but only 12.4 GLY,14.9 GLY,15.7 GLY and 12.4 GLY+THR diet programs differed significantly from the control. These results were in line with the findings of Kamran et al (2010) and Ferguson et al (1998a), but not completely in line with Moran et al (1992), Elwinger andSvensson (1996), Ferguson et al (1998b), Khajali and Moghaddam (2006) and Ospina-Rojas et al (2012), who noted also a lower total nitrogen content but no change in the moisture content of the litter because of supplementing low-protein diets.…”
Section: Ospina-rojas Et Al (2013) Also Reported That the Dietary Resupporting
confidence: 89%
See 4 more Smart Citations
“…All low-protein treatments numerically had a higher dry matter litter content than the control, but only 12.4 GLY,14.9 GLY,15.7 GLY and 12.4 GLY+THR diet programs differed significantly from the control. These results were in line with the findings of Kamran et al (2010) and Ferguson et al (1998a), but not completely in line with Moran et al (1992), Elwinger andSvensson (1996), Ferguson et al (1998b), Khajali and Moghaddam (2006) and Ospina-Rojas et al (2012), who noted also a lower total nitrogen content but no change in the moisture content of the litter because of supplementing low-protein diets.…”
Section: Ospina-rojas Et Al (2013) Also Reported That the Dietary Resupporting
confidence: 89%
“…In general, lower dietary crude protein levels seem to reduce the N content of the litter (Elwinger and Svensson, 1996;Fergusson et al, 1998a,b;Khajali andMoghaddam, 2006 andOspina-Rojas et al, 2012), and our results confirmed that as well. Ferguson et al (1998a) reported that a 2% reduction in dietary crude protein decreased litter ammonium-N and nitrogen concentration by 31 and 16%, respectively.…”
Section: Ospina-rojas Et Al (2013) Also Reported That the Dietary Resupporting
confidence: 89%
See 3 more Smart Citations